Humanidades Digitais e História da Ciência: um diálogo em construção - Mattos, Bruno Marques de (2024)
This research aims to analyze the use of Digital Humanities, one of the fastest growing academic fields in the main teaching and research institutions around the world, in the area of History of Science. To this end, the path taken by scholars and supporters in the development of this area of study was observed, from the first projects, through publications and major events, to the present day. Some lines of research in Digital Humanities were explored and analyzed, especially textual analysis and network study. Digital Humanities has the difficult mission of adapting digital technologies (with their innovative tools and methodologies) to the needs of the study of humanities in analyzing large and growing amounts of texts quickly and accurately